Analysis of dynamic splitting tensile failure and energy evolution characteristics of Jinping marble - Fengchen MIAO; Zhiliang WANG; Pan SUN; Songyu LI; Jingjing FU (Shuiwen dizhi gongcheng dizhi, 2024)
Splitting tensile failure is one of the main forms of instability failure of tunnel surrounding rock. At present, the mechanisms of rock crack propagation and energy evolution at the corresponding stages under dynamic splitting conditions have been rarely addressed. In this study, the splitting tests were carried out on Jinping marble samples using a split-Hopkinson pressure bar under different striking velocities. The dynamic damage processes of the samples were simulated with the ANSYS/LS-DYNA finite element software. From the perspectives of loboratory tests and numerical calculations, the mechanism of crack propagation and the characteristics of energy evolution during the splitting process of marble were comprehensively analyzed. The results show that the dynamic tensile strength of marble is linearly and positively related to the strain rate in the range of 5 s−1 to 35 s−1. The strain rate sensitivity of the Jinping marble is relatively low compared with the marbles of other regions. With the increase of the striking velocity, both the internal energy and kinetic energy of the system increase. At the moment of sample failure, the internal energy of the system drops to a minimum. Based on the calibrated parameters of Cowper-Symonds constitutive model, the final failure modes of the numerically simulated samples are basically consistent with the observed ones in the experiments. The research results of this study can provide guidance and reference for specific engineering applications.